The larvae of Polydora ciliata Johnston and Polydora hoplura Claparede - Wilson, Douglas P. (Journal of the Marine Biological Association of the United Kingdom, 1928)
The developments of Polydora ciliata Johns, and Polydora hoplura Clap, are described from the egg to a very late planktonic stage in the case of the former, and to young metamorphosed individuals in the case of the latter. Only external characters are described. In both species the eggs are laid in egg-sacs attached to the wall of the parent's burrow. The larvae of P. ciliata are released at a stage with three chsetigerous segments and lead a long planktonic life. The larvae of P. hoplura are provided with special food in the form of yolk-masses ; they undergo most of their development while in the protecting burrow of their parent; are released at a very late stage, and have only a short planktonic life. The larvae of both species have a complicated vestibule surrounding the mouth, and are provided with special sensory cilia on the head. The larvae are provided with a special kind of cilia, situated at the ends of every nototroch, which are used to take hold of the long provisional bristles in swimming. This suggests that one of the functions of the long bristles is that, in conjunction with these grasping-cilia, they increase the rigidity of the swimming larva, and hence the efficiency of its driving cilia. Previous references to Polydora larvae are briefly discussed.
World Polychaeta Database (WPolyDb)